-Symmetric diamines and their derivatives as promising organocatalysts for asymmetric synthesis. (November 2015) - Zlotin, S G; Kochetkov, S V
Abstract : The review is devoted to the application of -symmetric diamines and their derivatives as organocatalysts for asymmetric reactions (aldol, Michael, Mannich, Diels – Alder reactions, desymmetrization, allylation, etc. ). Amino acid derivatives, di- and polyamides (sulfamides), bisureas, bisthioureas, bisamidines and bisguanidines are considered. Significant attention is given to the effect of the catalyst structure on the mechanism of catalytic action. Successful applications of such catalysts in enantioselective synthesis of chiral biologically active compounds are summarized. The bibliography includes 181 references.